Bauen mit Beton im Kreislauf - Recycling, Re-Use und Ressourcenschonung 19. Symposium Baustoffe und Bauwerkserhaltung, Karlsruher Institut für Technologie (KIT), 9. März 2023 - Nolting, Ulrich; Dehn, Frank; Kind, Vanessa Mercedes (KIT Scientific Publishing, 2023)
The concrete industry is facing the major challenge of drastically reducing CO₂ emissions and thus contributing to sustainability and climate protection. In these conference proceedings, we would like to focus on how we can make the concrete industry not only more sustainable but also more cost-efficient by adopting the circular economy in the building sector. In particular, we focus on the recycling of concrete and the reuse of entire concrete components.